'Understanding the effects of social capital on social innovation ecosystems in Latin America through the lens of Social Network Approach'. Issue 1 (2nd January 2019) - Alcaide Lozano, Vanessa; Moliner, Liliana Arroyo; Murillo, David; Buckland, Heloise
ABSTRACT: This paper explores the role of social capital in creating social innovation ecosystems and fostering social impact. We examine two cases, chosen for their pioneering experiences in the field of tackling poverty in Latin America: Socialab and Compartamos con Colombia. Focusing on their structure of interactions (through network-level and node-level indicators), we examine the structural characteristics of the two ecosystems studied. We then correlate relational data to study the association between perceived social impact and the structural aspects. Results confirm heterophilic ecosystems and high levels of perceived impact as good drivers for strengthening future collaborations.